Characteristics of Irradiated Hydrogel Formulated from Composite i/k-carrageenan Combined with Polyvinyl Alcohol - Bagus Sediadi Bandol Utomo; Dina Fransiska; La Ode Sumarlin; Ihya Sulthonuddin (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2021)
Eucheuma seaweed from tropical waters habitat mainly contains carrageenan, a type of hydrocolloid potential for hydrogel production. This study aims to determine the characteristics of hydrogel formulated from composite i- and k-carrageenan combined with polyvinyl alcohol (PVA) which, could be used further for wound dressing application. The concentrations of composite i/k-carrageenan used were 1.0%, 1.5%, 2.0%, 2.5% and 3.0% w/w, and the PVA concentration was 12.5% w/w. Composite i/k-carrageenan in a proportion of 6:4 by weight. The hydrogel was irradiated using 60Co g-rays with the irradiation dose of 25 and 2 kGy.h-1. The concentration of composite i- and k-carrageenan influenced the gel fraction, water holding capacity, tensile strength, elongation, and surface morphology of the hydrogel. The optimum formula of irradiated composite hydrogel was obtained from 3.0% w/w of composite i/k-carrageenan. The formula had a gel fraction of 61.67%, water holding capacity of 1067.12%, tensile strength of 32.37 x 10-3 MPa, and elongation of 251.67%. Interestingly, the product with the optimum formula had a porous surface morphology and transparency, which are applicable for wound dressing purposes.